The effect of intravitreal ranibizumab on apoptosis induction in rat retinal tissue - Machalińska, Anna; Pius-Sadowska, Ewa; Sekrecki, Michał; Kawa, Miłosz P.; Rogińska, Dorota; Machaliński, Bogusław (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Purpose : Despite the rapidly accumulating knowledge on pharmacokinetic properties and dosage of ranibizumab, the influence of this vascular endothelial growth factor inhibitor on retinal cell survival/apoptosis homeostasis remains unclear. The aim of this study was to investigate the biological effects of a single intravitreal injection of ranibizumab on retinal tissue with a focus on apoptosis-related signaling pathways in the rat retina. Material and methods : Male Wistar rats were treated with an intravitreal injection of ranibizumab or anti-rat vascular endothelial growth factor antibody in the right eye. The left eyes were injected with the same volume of physiological saline. On the 3rd and 7th day post-injection, the eyes were enucleated, and the retinas were isolated for further molecular analysis of the expression of selected apoptosis-related molecules at mRNA (BAX, BCL-2) and protein (caspase-3) levels using quantitative RT-PCR and western blot techniques, respectively. Results : Following a 3-day-exposure to ranibizumab at the established concentration, the BAX/BCL-2 mRNA expression ratio was significantly increased compared to the saline-treated controls and the healthy control eyes. Furthermore, on day 3. post ranibizumab injection, caspase-3 cleavage, detected qualitatively using western blotting, confirmed potential activation of the irreversible phase of apoptosis. In contrast, on day 7. post-injection, there were no significant differences in the BAX/BCL-2 mRNA expression ratios or caspase-3 cleavage between different groups. Conclusions : Intravitreal administration of ranibizumab leads to a transient induction of apoptosis in retinal cells, with an onset directly after the vascular endothelial growth factor inhibitor administration and apparent down-regulation shortly afterwards. These results must be considered when intravitreal injections of ranibizumab are administered to treat retinal diseases.